"Formal Thought Disorder" in a General-Community Sample With Elevated Schizotypal Traits. Issue 5 (May 2019) - Deyo, Cliff; Langdon, Robyn
Abstract : Abstract: Different dimensions of formal thought disorder (FTD) are distinguished by different patterns of cognitive dysfunction and cortical variability in patients with schizophrenia; however, inconsistent findings may relate to patient-related confounds. Investigating FTD in nonpatient samples with elevated levels of schizotypal traits avoids these confounds, but its utility to FTD research is unknown. Thus, we performed principal components analysis (PCA) of FTD ratings using the Scale for the Assessment of Thought, Language, and Communication (TLC) and the Thought and Language Index (TLI) in a general-community sample with elevated schizotypal traits. Both scales showed "clinically elevated" FTD, particularly, the TLC. PCA described a three-component TLC solution ("disorganization, " "verbosity, " "emptiness") and a two-component TLI solution ("negative, " "idiosyncratic"), generally consistent with schizophrenia research. TLC "disorganization" and "emptiness" were correlated with psychosis-like experiences. TLI "negative" was associated with lower general cognitive function, consistent with schizophrenia research. FTD may have shared etiology along the schizophrenia spectrum. Abstract : Supplemental digital content is available in the text.